Short stature with precocious puberty caused by aggrecan gene mutation: A case report. Issue 34 (21st August 2020) - Wang, Yuanyuan; Ge, Juan; Ma, Jianying; Qiao, Lingyan; Li, Tang
Abstract: Introduction: The present study is carried out to review the clinical data and gene detection results of a pediatric patient with short stature, and to summarize the relationship between clinical phenotype and genotype of the child with Aggrecan (ACAN) gene mutation. Patient concerns: Our study was started with the observation and follow-up of a 5-year-4-month-old full-term child with short stature accompanied by central precocious puberty (CPP). Diagnosis: Gene sequencing showed that there was a new heterozygous mutation C.2164C >G(p.P722A) in exon 11 of ACAN gene, which was inherited from her father. Interventions: The child was treated by growth hormone for 6 months with mild growth, and accelerated bone age (BA) after the presence of precocious puberty. The child was diagnosed with CPP, and was provided with combined gonadotropinreleasing hormone (GnRH) therapy. Outcomes: The height of the pediatric patient was 99.4 cm (-3.13SDS) on admission, which was 111.9 cm (-2.08SDS) at the age of 6 years and 10 months, with a growth rate of 8.1 cm/year. There was no significant increase in BA of the pediatric patient after 1 year of follow-up. Conclusion: Literature review indicated that the clinical manifestations of ACAN gene mutation are the most common in idiopathic short stature, most of which are familial inheritance and can also be sporadic. Some children may also have osteoarthritis, disc herniation or degeneration. In most cases, children may have advanced BA, and retardation of BA is also found in some cases. To sum up, growth hormone combined with GnRH analogue treatment can effectively improve body height of children by postponing their adolescence. Meanwhile, ACAN gene mutation shall be considered for small-for-gestational-age children without significant growth catch-up and with family history.